Hydrogeochemistry of low agricultural soil yield in Sahelian and sub-tropical watersheds, Northern Cameroon. (March 2023) - Fantong, Wilson Y.; Chounna, Gergino; Nenkam, Therese.L.L. Jokam; Fouepe, Alain T.; Fru, Ernest Chi; Vassolo, Sara; Montcoudiol, Nelly; Fodoue, Yaya; Haman, Jean Blaise D.; Carlier, Claire; Nbendah, Pierre; Nkeng, George E.
Abstract: Bound to the north by the Sahara and to the south by the Sudanian savannah, watersheds in the African Sahelian belt supply food and water to an estimated 135 million people. Being one of the Earth's most vulnerable zones to climate change impacts, the Sahel covers a 3.1 million km 2 corridor from the Atlantic Ocean in the west to the Red Sea in the east. It is predicted that decadal timescale migration of Sahelian arid conditions southwards, and associated changes in water-rock interaction patterns resulting from desertification and reduction in rainfall trends, would increasingly alter soil nutrients availability. In this pilot study, we developed a hydrogeochemical approach by linking local geology to elemental dynamics, while focusing on nutrient enrichment, depletion, mobility, flux, and exchange between bedrock and groundwater. This approach was successfully applied to two watersheds in Northern Cameroon: the Sahelian Douka Longo sedimentary watershed (SDLSW) and the tropical Bidou igneous watershed (TBIW). Comparative inorganic nutrient budgets and availability suggest that carbonates and plagioclases are prone to weak and intermediate chemical weathering, compared to stronger rates recorded for granite, basalt, trachyte, and sandstone. Collectively, these sources contribute to significant trace element nutrients enrichment of local water bodies within the watersheds. Non-isochemical dissolution produces highly mobile Ca, Mn, Na, Cu, Zn, K, Ni and Fe compared to elements not part of plant nutrients. Acidic groundwater recharged by rainwater through preferential flow pass has a Ca + Mg–NO3 and Ca + Mg–HCO3 chemical signature in the SDLSW and the TBIW, respectively. Both watersheds are characterised by distinct solute flux patterns, with lower annual nutrient loss rates associated with the TBIW. The data indicate that surface water runoff needs to be managed to control nutrient deficiencies and excesses, and that low-yield capacity in both watersheds appear to be partly linked to P, Fe, and Mo deficiencies.